3D plants: the impact of integrating science, design, and technology on high school student learning and interests in STEAM subjects and careers - Sandra Arango-Caro; Tiffany Langewisch; Kaitlyn Ying; Michelle Arellano Haberberger; Nate Ly; Christopher Branton; Kristine Callis-Duehl (Disciplinary and Interdisciplinary Science Education Research)
Abstract STEAM education is an educational approach of interdisciplinary teaching of science, technology, engineering, art, and mathematics. STEAM education, however, is often viewed as only including art elements into STEM teaching. Without true integration of the disciplines in STEAM curricula, students rarely are exposed to the connection among disciplines, and self-identify as solely scientists, artists, or technophiles. STEAM curricula also infrequently integrate design, which promotes creativity and innovation. Effective STEAM curriculum and practices are needed to prepare students to face 21st century challenges and work demands. We designed a high school STEAM educational module that integrated plant science, design, and emergent technologies through the creation of 3D models of plants and augmented and virtual reality (AVR) experiences and investigated its impact on students’ understanding of the intersection of art and design with science, learning and skills gains, and interests in STEAM subjects and careers. The module used a project-based learning approach that relied on student teamwork and facilitation by educators. In this 3D plant modeling module, students: (1) investigated plants under research at a plant science research center, (2) designed and created 3D models of those plants, (3) learned about the application of 3D modeling in AVR platforms, and (4) disseminated project results. We used qualitative and quantitative research methods both before and after the implementation of the model to assess the impact of the 3D modeling module. Student responses revealed that approximately half of the students had a good understanding of the intersection of art and design with science prior to the implementation of the module, while the other half gained this understanding after completing their projects. Students saw art and design playing a role in science mainly by facilitating communication and further understanding and fostering new ideas. They also reported that science influenced art and design through the artistic creation process. The most common learning gains were in plant science and 3D modeling, with 35% and 20% of the students reporting these themes only after completing their projects, respectively. The skill gains most cited were research, teamwork, and communication skills. Over 25% of the students reported these skill gains only after the completion of their projects. Paired comparisons of survey responses indicated a significant increase in students’ interest in science, mathematics, and design subjects after they completed their projects. At the end of the module, 40% of the students were more interested in STEAM careers. Another 13% of the students indicated they already had an interest in STEAM careers before beginning the module. Our findings indicate that our STEAM module effectively integrated science, art, design, and technology, enhancing student literacy in these fields, and providing students with essential 21st century skills. The module led to interdisciplinary learning and development of interest in STEAM subjects and careers. The combination of pedagogical strategies used in our module for active, collaborative, authentic, and meaningful learning exemplifies an effective STEAM curriculum with valuable instructional tools for educators, inspiring new ways of teaching and learning, contributing to the practice and applications in STEAM education.